2014
DOI: 10.1063/1.4892364
|View full text |Cite
|
Sign up to set email alerts
|

Near-field resonance shifts of ferroelectric barium titanate domains upon low-temperature phase transition

Abstract: Scattering scanning near-field optical microscopy (s-SNOM) has been established as an excellent tool to probe domains in ferroelectric crystals at room temperature. Here, we apply the s-SNOM possibilities to quantify low-temperature phase transitions in barium titanate single crystals by both temperature-dependent resonance spectroscopy and domain distribution imaging. The orthorhombic-to-tetragonal structural phase transition at 263 K manifests in a change of the spatial arrangement of ferroelectric domains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…The first study of low‐temperature s‐SNOM was performed by Yang et al, and the study involved the s‐SNOM imaging of V 2 O 3 during the IMT at ≈200 K ( Figure a) . In the following year, Döring et al performed the s‐SNOM imaging of the barium titanate ferroelectric domain at ≈222 K (Figure b) . In 2016, McLeod et al set a milestone by systematically demonstrating the use of s‐SNOM to study SCQM and observed the IMT of V 2 O 3 at 160–180 K with high spatial resolution and SNR (Figure c) .…”
Section: Current Stagementioning
confidence: 99%
“…The first study of low‐temperature s‐SNOM was performed by Yang et al, and the study involved the s‐SNOM imaging of V 2 O 3 during the IMT at ≈200 K ( Figure a) . In the following year, Döring et al performed the s‐SNOM imaging of the barium titanate ferroelectric domain at ≈222 K (Figure b) . In 2016, McLeod et al set a milestone by systematically demonstrating the use of s‐SNOM to study SCQM and observed the IMT of V 2 O 3 at 160–180 K with high spatial resolution and SNR (Figure c) .…”
Section: Current Stagementioning
confidence: 99%
“…The mapping of the nanoscale topography and the local piezo-response were performed with a custom-made low-temperature AFM 36 37 on as-grown (001) and (111) surfaces of single crystalline GaV 4 S 8 samples [see Fig. 1(e–g) ].…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14][15] Wavelength-independent spatial resolution in the order of ∼ 10 nm has been demonstrated via s-SNOM and nano-FTIR for different material systems, such as metal/nonmetal structures, [16][17][18][19] organic 16,20 and biological materials, 1,21,22 semiconductors, 18,23 and ferroelectric domain structures. [24][25][26][27] Close to material resonances such as plasmon and phonon modes, signal strength and material contrast in s-SNOM can be strongly enhanced. 17,[24][25][26][27][28][29][30][31] At infrared wavelengths, this mechanism is highly sensitive to the material properties and may be applied to polar materials, 28,31 metals, semiconductors, 18,23 and biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Close to material resonances such as plasmon and phonon modes, signal strength and material contrast in s-SNOM can be strongly enhanced. 17,[24][25][26][27][28][29][30][31] At infrared wavelengths, this mechanism is highly sensitive to the material properties and may be applied to polar materials, 28,31 metals, semiconductors, 18,23 and biological samples. 1, 21,22 Resonant excitation even allows for the local characterization within the very same material, e.g.…”
Section: Introductionmentioning
confidence: 99%